The Christocentric cosmology of St. Maximus the Confessor - Tollefsen, Torstein, 1953- (Oxford ; New York : Oxford University Press, 2008)
Maximus the Confessor (580-662) was an important Byzantine thinker, the 'father of Byzantine theology'. This text describes his metaphysical world-view. The discussion covers Maximus' doctrine of creation, the Logos and the logoi, the cosmic order, the activities or energies of God, and how created beings may participate in God.
The divine ideas and the creation of the cosmos -- The logos, the logoi, and created beings -- The divine activity -- The concept of participation.
Includes bibliographical references (p. [231]-238) and index.
Description based on print version record.
Keywords: Maximus, -- Confessor, Saint, -- ca. 580-662.; Metaphysics; Cosmology; Cosmology; Maximus, Confessor, Saint, ca. 580-662.; Metaphysics; Religion; RELIGION -- Christian Theology -- Systematic; RELIGION -- Christianity -- General; Electronic books